Protests against American civil government in the island of Cebu, Philippine Islands. Translation of the proceedings of the municipal governments of the island of Cebu, Philippine Islands, protesting against the establishment of American civil government therein (United States. 56th Congress, 2d Session. Senate. Document, 1901)
The undersigned, members of the popular junta (municipal council) of Danao, of this province, declare that they objected to taking the required oath of allegiance to America. They state that for objecting to this they were thrown into prison and were obliged to work in an objectionable and mortifying way from the 9th day of August to the 25th of September. That they refused to take the oath at first because it was contrary to their inner belief, and thus perjury. But after great suffering and illtreatment they were obliged to take the oath under duress. They do not desire to take the oath, because they do not desire to undergo the same treatment as their mayor, Senor victorino Buot, and the delegate of justice, Felix Batucan, who, having refused to sign, were taken from prison and sent to the capital of this island as prisoners. (Excerpt from the book)